The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cancers13081876
|View full text |Cite
|
Sign up to set email alerts
|

Eye Tumors in Childhood as First Sign of Tumor Predisposition Syndromes: Insights from an Observational Study Conducted in Germany and Austria

Abstract: Retinoblastoma and other eye tumors in childhood are rare diseases. Many eye tumors are the first signs of a genetic tumor predisposition syndrome and the affected children carry a higher risk of developing other cancers later in life. Clinical and genetic data of all children with eye tumors diagnosed between 2013–2018 in Germany and Austria were collected in a multicenter prospective observational study. In five years, 300 children were recruited into the study: 287 with retinoblastoma, 7 uveal melanoma, 3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 54 publications
0
22
0
1
Order By: Relevance
“…Da es sich bei etwa 40 % der Fälle um hereditäre Retinoblastome handelt, spielt -insbesondere bei bilateraler Erkrankung -die Genetik eine große Rolle [4]. Retinoblastome entstehen durch ein abnormes und unkontrolliertes Wachstum von Retinoblasten, retinalen Vorläuferzellen, aufgrund einer Mutation im RB1-Tumorsuppressions-Gen auf Chromosom ten Chemotherapeutikums in den Tumor zu ermöglichen [9].…”
Section: Das Retinoblastomunclassified
“…Da es sich bei etwa 40 % der Fälle um hereditäre Retinoblastome handelt, spielt -insbesondere bei bilateraler Erkrankung -die Genetik eine große Rolle [4]. Retinoblastome entstehen durch ein abnormes und unkontrolliertes Wachstum von Retinoblasten, retinalen Vorläuferzellen, aufgrund einer Mutation im RB1-Tumorsuppressions-Gen auf Chromosom ten Chemotherapeutikums in den Tumor zu ermöglichen [9].…”
Section: Das Retinoblastomunclassified
“…In childhood, malignant eye tumors have been associated with genetic tumor predisposition syndrome [ 6 , 7 ]. Genetic tumor predisposition syndrome is a genetic condition caused by inherited mutations in a group of genes that increase the risk of developing certain types of tumors [ 6 , 8 ]. It has been suggested that inherited eye disorders are the leading cause of blindness in childhood in developed countries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…And he was asked to follow up by outpatient visit every month. Medulloepithelioma of ciliary body is a rare intraocular tumor arising from the nonpigmented ciliary epithelium of pars plicata and only nearly 120 cases were reported all over the world [1][2][3][4][5][6] . The tumor is believed to be nonhereditary, but it mainly occurs in infant and children, at a median age of 2 to 5y [1,5,[7][8][9][10][11] .…”
mentioning
confidence: 99%